Design and adsorption of modular engineered proteins to prepare customized, neuron-compatible coatings - Straley, Karin S.; Heilshorn, Sarah C. (Frontiers in Neuroengineering, 2009)
Neural prosthetic implants are currently being developed for the treatment and study of both peripheral and central nervous system disorders. Effective integration of these devices upon implantation is a critical hurdle to achieving function. As a result, much attention has been directed towards the development of biocompatible coatings that prolong their in vivo lifespan. In this work, we present a novel approach to fabricate such coatings, which specifically involves the use of surface-adsorbed, nanoscale-designed protein polymers to prepare reproducible, customized surfaces. A nanoscale modular design strategy was employed to synthesize six engineered, recombinant proteins intended to mimic aspects of the extracellular matrix proteins fibronectin, laminin, and elastin as well as the cell-cell adhesive protein NCAM (neural cell adhesion molecule). Physical adsorption isotherms were experimentally determined for these engineered proteins, allowing for direct calculation of the available ligand density present on coated surfaces. As confirmation that ligand density in these engineered systems impacts neuronal cell behavior, we demonstrate that increasing the density of fibronectin-derived RGD ligands on coated surfaces while maintaining uniform protein surface coverage results in enhanced neurite extension of PC-12 cells. Therefore, this engineered protein adsorption approach allows for the facile preparation of tunable, quantifiable, and reproducible surfaces for in vitro studies of cell-ligand interactions and for potential application as coatings on neural implants.